If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(h+2)=3h-2)
We move all terms to the left:
4(h+2)-(3h-2))=0
We multiply parentheses
4h-(3h-2))+8=0
| -u-5=10+3-3u | | 1.5+x/6=2.4 | | -14=-(x+7)-(1-3x) | | 1/2x-9=7.5+6x | | x+20+2x+40=180 | | 10x+5-8x=-19 | | 1-3j=13 | | x+x+x+x+x=28 | | 13b-12b=13 | | 3(3x-1)=1 | | 2x+9/4x=34 | | 3-2(2x+5)=2(3x+6) | | R(q)=q²-13q+90 | | 1-4x=2(-2+x) | | 9n−24= | | -10+7n=10+10n+7 | | 16=-5a-3a | | 32x+6=34x-2 | | x+7=−6−12 | | 30÷n=360 | | -0.1x=-2 | | 7x-0(4x+3)=15 | | (7x-2)(x-6)=0 | | t/3+7=8 | | 9x-12=-2x+65 | | 120=2x-108 | | 10x+3=331 | | P+p=163p-6= | | 1/4(x+3)=3(x+3) | | 3(2x-5)=2=23 | | -15=4x+3 | | 8x+12-3x=67 |